Reducing stomatal density by expression of a synthetic epidermal patterning factor increases leaf intrinsic water use efficiency and reduces plant water use in a C4 crop - Ferguson, John N (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology.